Advancing supply chain integrity and traceability through blockchain integration - Zherzherunov, P.; Shmatko, O. V.; Шматко, О. В. (P.C. Publishing House; UKRLOGOS Group, 2025)
Blockchain technology is reshaping supply chain management (SCM) by enhancing transparency, traceability, and trust among stakeholders. This study reviews recent applications of blockchain in SCM, focusing on its integration with IoT, smart contracts, and distributed ledger technologies. Key benefits include real-time data sharing, tamperproof records, and improved coordination across supply chain actors. The article proposes a conceptual blockchain-based model that supports secure data exchange, automated verification, and tokenized asset tracking, aimed at reducing fraud and inefficiencies. Despite its potential, blockchain implementation faces challenges such as scalability, regulatory uncertainty, and interoperability. Through analysis of recent case studies and pilot projects, the paper identifies practical limitations and future directions, including the development of lightweight consensus algorithms and ethical frameworks for decentralized systems. The findings underscore blockchain’s capacity to modernize supply chains, provided that technical and institutional barriers are addressed.